2017
DOI: 10.1021/acs.energyfuels.7b00121
|View full text |Cite
|
Sign up to set email alerts
|

A-Site Excess (La0.8Ca0.2)1.01FeO3−δ (LCF) Perovskite Hollow Fiber Membrane for Oxygen Permeation in CO2-Containing Atmosphere

Abstract: CO 2 -resistant oxygen selective ceramic membranes show potential to be utilized in clean combustion and membrane-based reactions for greener chemical synthesis. In real applications, such membranes should have high mechanical strength as well as high oxygen flux and high stability in a CO 2 -containing atmosphere. In this work, a (La 0.8 Ca 0.2 ) 1.01 FeO 3−δ (LCF) perovskite hollow fiber membrane was developed. Its oxygen permeation behavior was tested in different gas atmospheres, i.e., helium and carbon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…When looking at the Figure 5a, the phenomena of these three stages are clearly observed. Figure 5a also compares the oxygen flux values of two kinds of LCF hollow fiber membranes from (La 0.8 Ca 0.2 ) 1.01 FeO 3−δ (1% A-site cation surplus in ABO 3 from literature measured at 950 • C) and La 0.8 Ca 0.2 Fe 0.94 O 3−δ (6% B site cation deficiency) operated at relatively similar conditions [41]. Apparently, the latter composition has a larger flux than the former as more oxygen vacancies were created by the B-site cation deficiency.…”
Section: Oxygen Permeation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at the Figure 5a, the phenomena of these three stages are clearly observed. Figure 5a also compares the oxygen flux values of two kinds of LCF hollow fiber membranes from (La 0.8 Ca 0.2 ) 1.01 FeO 3−δ (1% A-site cation surplus in ABO 3 from literature measured at 950 • C) and La 0.8 Ca 0.2 Fe 0.94 O 3−δ (6% B site cation deficiency) operated at relatively similar conditions [41]. Apparently, the latter composition has a larger flux than the former as more oxygen vacancies were created by the B-site cation deficiency.…”
Section: Oxygen Permeation Testmentioning
confidence: 99%
“…For the hollow fiber membrane with wall thickness of 0.25 cm, under air/helium gradient and at 850 • C, the oxygen flux is 2.20 mL min −1 cm −2 ; however, the flux would be reduced to zero once the sweep gas was switched to CO 2 due to the high basicity of Ba and Sr, causing a fast carbonate formation on the membrane surfaces [41]. One strategy to overcome poor stability is to tailor the ABO 3 composition with less CO 2 -sensitive elements like La and Ca and without cobalt [25,40,41]. For example, BaCe x Fe 1−x O 3−δ (BCF) displayed a higher stability even in H 2 -containing atmosphere [42].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, surface exchange reaction becomes the rate limiting step for permeation through hollow fiber (Han et al, 2016;Zhang et al, 2015). To enhance the permeation rate further, surface modification approach can be performed such as the surface roughening achievable via acid etching (Yang et al, 2017) or methane activation (Liu et al, 2009) and the deposition of porous metal oxide layer or active noble metal(s) or transition metal(s) on the surface (Han et al, 2015;Zhang et al, 2015;Na et al, 2017). Sase et al previously reported the accidental formation of perovskite oxide/Ruddlesden-Popper oxide heterophase interfaces of La0.6Sr0.4CoO3/(La,Sr)2CoO4 (LSC113/LSC214) at the surface of 1400 o C sintered La0.6Sr0.4CoO3 disk (Sase et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The polymeric-based perovskite hollow fiber membrane precursor was formed by spinning a polymer solution within the coagulant, i.e., water (Han et al, 2016;Han et al, 2015). Due to the binding capability of polyethersulfone (PESf), a large amount of water-insoluble inorganic perovskite powder can be homogeneously incorporated within the polymer solution to form a spinning dope from which the hollow fiber precursor was produced (Han et al, 2016;Yang et al, 2017). Here, such precursors were made by mixing LSC113 powder and a polymer solution of PESf and 1-methyl-2pyrrolidinone (NMP) (Han et al, 2016).…”
Section: Hollow Fiber Morphologymentioning
confidence: 99%
“…Surface modification has been reported as a practical method to achieve high oxygen permeation rate at lower temperature via the surface reaction kinetics enhancement, that is, improved oxygen exchange reaction rate or oxygen adsorption/desorption rate . Such a modification can be achieved either by increasing the surface area, that is, via acid‐etching or methane activation or by depositing catalyst on the membrane surface, that is, via depositing porous metal oxide layer, or applying short‐circuit decoration . When surface decoration material that has different phase to the membrane material is used, hetero‐interface manifests; the presence of which has been associated with a significantly enhanced surface reaction rate .…”
Section: Introductionmentioning
confidence: 99%